Romania Toward a Low Carbon and Climate Resilient Economy : Forestry Sector Analysis - World Bank (World Bank, Washington, DC, 2016)
This report is about forests that provide a substantial contribution to mitigation in Romania by sequestering carbon, helping to counter carbon emissions from other sectors in the economy. Sustainable forest management is challenged by fragmented ownership and insufficient financial resources in particular. A summary of key existing analytic studies, and the construction of a marginal abatement cost curve for mitigation actions in the forestry sector, was the basis for identifying key adaptation and mitigation measures for Romania’s forests. In addition to the national and international analytic exercises, a marginal abatement cost curve (MACC) was estimated for three measures: afforestation, sustainable management of protection forests, and sustainable management of production forests. The key findings were as follows: (i) analysis of adaptation needs and mitigation possibilities found that forestry could provide cost-efficient abatement for Romania; and (ii) financing needs for the three priority measures, afforestation, sustainable management of protection forests, and sustainable management of production forests were evaluated. The conclusions and recommendations were as follows: (i) recommendations stress the importance of sustainable forest management for Romania and the European Union's (EU) desirability to move rapidly towards defining the rules for Land Use, Land Use Change and Forestry (LULUCF) based mitigation within its 2030 framework; (ii) policy measures that mitigate climate change and contribute to growth are critical, as is capacity building; and (iii) a greener path for forests will require additional public spending.